UPAYA MENINGKATKAN KARAKTER SISWA GEMAR MEMBACA MELALUI PEMBERDAYAAN PERPUSTAKAAN BERTARAF NASIONAL DI SD MUHAMMADIYAH 1 ALTERNATIF KOTA MAGELANG TAHUN AJARAN 2021/2022 - Ratih Laksmiwati Nugroho; Suhartono Suhartono; Kartika Chrysti Suryandari (Universitas Sebelas Maret, 2022)
National school library standard is one the efforts to develop a love of reading. The study aimed to describe the efforts to develop a love of reading in students through national school library standard, to describe the impact of efforts to develop a love of reading in students through national school library standard, and to analyze the obstacles and solutions faced in SD Muhammadiyah 1 Alternatif Kota Magelang. It was a qualitative research with case study method. The collection techniques were observation, interviews, document studies, and questionnaires. The results indicated that six components to develop a love of reading in students through national school library standard were the collection components, facilities and infrastructure, library services, librarian, library administration, management, and performance strengthening. The positive impacts of school library in developing a love of reading were divided into six indicators which each indicator achieved high percentage: visiting the library had 61.1%, library utilization got 68%, borrowed books had 54.9%, having interest in books and libraries got 87.4%, having books owned by the students got 56.6%, and the frequency of students in reading books had 83.4%. In addition, there was a positive impact in improving the Indonesian learning outcomes to fifth grade students from 86.12 to 86.96. The positive impacts of library affected on students’ skills observed from the work on the wall magazine. The students developed in reading activities, writing activities, observing activities, and analyzing activities. Keywords: national school library standard, a love of reading, knowledge, skills.